Edukasi Penggunaan Instalasi Listrik Yang Baik Untuk Menghindari Bahaya Kebakaran Akibat Listrik Di Kelurahan Gondrong Kecamatan Cipondoh Kota Tangerang - Mauriraya, Kartika Tresya; Afrianda, Rio; Pasra, Nurmiati; Pahiyanti, Novi Gusti; Makkulau, Andi; Fernandes, Alex; Sukmajati, Sigit (TERANG, 2020)
This community partnership program aims to help the public to know the security of residential installations and fire prevention efforts due to an electrical surge. As well as providing motivation to be able to continue to encourage and apply to the community in the partner area to always prevent fires due to electrical short circuit and use electrical equipment according to standards. With the partnership program activities of the community in the Gondrong neighborhood, Cipondoh Sub-district will be able to provide education on integrated electrical installations to avoid fire hazards due to electricity